On the MMSE‐based multiuser millimeter wave MIMO hybrid precoding design - Elmagzoub, Hisham M (International journal of communication systems, 2020)
Summary A hybrid MMSE‐based precoder and combiner design with low complexity is studied in this paper for both the downlink and uplink multiuser millimeter wave MIMO systems. At first, according to the underlying channel knowledge, the phases of the RF precoder and combiner are manipulated by using the MMSE criterion. On the basis of the MMSE‐based analog precoder design, the MMSE‐based digital baseband precoder can be readily derived. Thus, this method combines the advantage of using the MMSE precoding and phase extraction technique to obtain a reasonable solution. The proposed hybrid precoding design will be examined in both the uplink and downlink multiuser MIMO systems. Numerical results are presented to show that the proposed MMSE‐based hybrid precoding design is capable of attaining superior performance in terms of both the spectral efficiency and energy efficiency over the existing designs. Moreover, we will show that the MMSE‐based design can be readily extended to the multiuser millimeter wave MISO systems when only statistical channel state information is available. In this paper, we propose an MMSE‐based hybrid precoding scheme in three different systems. The main idea of our proposed scheme is to manipulate the phase of the analog part by using the MMSE criterion. Motivated by the excellent performance of the MMSE method in conventional baseband precoder design, the MMSE criterion is used as a means of phase extraction. Our algorithm does not apply optimization techniques nor iterative methods. Therefore, a reasonable solution is given with low complexity.